Ethnobotanical survey of Hypolipidemic medicinal plants in Ghardaia Region, Algeria - Kedaid, Hafida; Toumi , Ikram; Kraimat, Mohamed; Adamou, Abdelkader; Mahamedi, Alla Eddine; Telli , Alia; Imelhayene, Meriem (Ethnobotany Research and Applications, 2026)
Background: Hyperlipidemia (HL) constitutes a significant risk factor for cardiovascular diseases. This lipid disorder has become a primary focus for researchers because of its high prevalence worldwide, prompting increased efforts to discover new treatment options originating from natural alternatives to synthetic medications that can have serious adverse effects. Ethnopharmacological and ethnobotanical approaches have played a key role in documenting and identifying medicinal and aromatic plants. This survey aims to document Algerian medicinal plants (MPs) reported by local populations in the Ghardaïa region (Southern Algeria) as effective for the management of HL. Methods: The survey was conducted from February 2023 to February 2024. Data were collected via semi-structured interviews with 184 participants and analyzed using Relative Frequency of Citation (RFC), Use Value (UV), and Informant Consensus Factor (ICF). Additionally, for each identified plant species, ethnobotanical characteristics were documented, including the plant parts used and preparation methods. Results: The investigation documented 48 species distributed across 28 families, with Lamiaceae and Apiaceae emerging as the dominant families. Additionally, several plants were documented for the first time in the management of HL, including Pituranthos chlorantus (Coss. and Dur.), Echinops spinosus L., and Fagonia glutinosa Del. Aerial parts were the most frequently used (30%), while infusion was the predominant preparation technique (40%). Quantitative analysis identified the species with the highest UVs as Pituranthos chlorantus (1.75), Mentha spicata L. (1.50), and Moringa oleifera Lam. (1.42). However, the highest Relative Frequency of Citation (RFC) values were for Citrus limon L. (RFC = 0.86), Pituranthos chlorantus, Solanum melongena L., Olea europaea L., and Camellia sinensis L. (each with RFC = 0.652). The highest agreement of diseases was hyperlipidemia and hyperglycemia (ICF = 0.98), followed by obesity and hypertension (ICF = 0.97). Conclusions: The documented medicinal flora provides valuable baseline data for researchers working in phytotherapy for cardiovascular diseases, obesity, hyperglycemia, hypertension, and hyperlipidemia. These species represent promising sources of novel bioactive compounds that may be developed into therapeutic agents. Keywords: Medicinal plants, traditional medicine, Hyperlipidemia, Ghardaia, Algeria